The roles of morphological awareness in academic writing through the mediation of productive vocabulary knowledge among L2 postgraduate students - Asaad, Hani Qasem Mohammed (2019)
Studies have found that morphology awareness could help writers in increasing productive vocabulary, reducing vocabulary errors, and making complex sentence structures using various forms of words. Postgraduate students as second language users of English (L2) were found to lack vocabulary and have difficulties in their academic writing. However, research on the relationship between morphological awareness and academic writing is considerably lacking as researchers have been focusing on examining the relationship between morphological awareness and reading comprehension, vocabulary reading, receptive vocabulary knowledge, and spelling. The study investigates the relationship between morphological awareness and academic writing. It examines the effect of morphological awareness intervention on L2 postgraduate students’ morphological awareness and academic writing, and the mediating role of productive vocabulary knowledge. The quasi experimental study involves two groups of L2 postgraduate students. The intervention includes eleven morphological awareness training sessions. Data obtained from the pre-test and post-test of both groups were analysed using statistical analysis SPSS version 25. The results reveal that the degree of morphological awareness prior to the morphological awareness intervention was low among the participants. The morphological awareness intervention was found to be very effective and significant especially among the students in the experimental group as it assisted them in increasing morphological awareness, improving productive vocabulary knowledge, and enhancing academic writing. The results also reveal that morphological awareness was significantly related to academic writing and productive vocabulary knowledge. Morphological awareness contributes indirectly to academic writing through the mediation of productive vocabulary knowledge. The intervention shows a significant effect on the participants’ performance in becoming better writers. The study suggests that teaching morphology plays a significant role in enhancing L2 postgraduate students’ academic writing and in improving their productive vocabulary knowledge. Hence, the study could serve as a base for future morphological awareness intervention.